Cellulose-based water purification using paper filters modified with polyelectrolyte multilayers to remove bacteria from water through electrostatic interactions. Issue 12 (16th October 2018) - Ottenhall, Anna; Henschen, Jonatan; Illergård, Josefin; Ek, Monica
Abstract : Bacteria are removed from contaminated waters through adsorption onto the modified cellulose fiber surface in paper filters with pores larger than the bacteria. Abstract : Filtration is a common way to obtain pure drinking water by removing particles and microorganisms based on size exclusion. Cellulose-based filters are affordable and biobased option for the removal of particles but bacteria are usually too small to be removed by size exclusion alone. In this article, the surfaces of cellulose fibres in two types of commercial paper filters have been given a positive net charge to trap bacteria through electrostatic interactions without releasing any biocides. The fibres were modified with the cationic polyelectrolyte polyvinylamine polymer in single layers (1 L) or in multilayers together with the anionic polyelectrolyte polyacrylic acid (3 L or 5 L) using a water-based process at room temperature. Filtration tests show that all filters, using both types of filter papers and a number of layers, can physically remove more than 99.9% of E. coli from water and that the 3 L modified filters can remove more than 97% of cultivatable bacteria from natural water samples. The bacterial reduction increased with increasing number of filter sheets used for the filtration and the majority of the bacteria were trapped in the top sheets of the filter. The results show the potential for creating water purification filters from bio-based everyday consumable products with a simple modification process. The filters could be used in the future for point-of-use water purification that may be able to save lives without releasing bactericides.